Fly ash-derived MCM-41 as a low-cost silica support for polyethyleneimine in post-combustion CO2 capture - Panek, R.; Wdowin, M.; Franus, W.; Czarna, D.; Stevens, L.A.; Deng, H.; Liu, J.; Sun, C.; Liu, Hao; Snape, Colin E. (Elsevier, 2017)
The mesoporous silicate molecular sieve, MCM-41, has been synthesized from pulverized coal fly ash (PFA), where the silicate filtrate used is a by-product from hydrothermal zeolite production. Rice husk ash was also used for comparison but fusion with sodium hydroxide was used to prepare the silicate filtrate, along similar lines to earlier reports of using PFA as a precursor for MCM-41 synthesis. The MCM-41 samples are chemically and mineralogically similar to a commercially available sample, but with higher pore volumes dominated by mesopores (0.92–1.13 cf. 0.88 cm3 g−1). After polyethyleneimine (PEI) impregnation for CO2 capture, the ash derived MCM-41 samples displayed higher uptakes than the commercial sample with the maximum achievable PEI loading of 60 Wt.% PEI (dry basis) before particle agglomeration occurs, approximately 13 compared to 11 Wt.%, respectively, the latter being comparable to earlier reports in the literature. The PFA sample that displays the fastest kinetics to achieve 90% of the equilibrium uptake had the largest mesopore volume of 1.13 cm3 g−1. Given the PFA-derived MCM-41 uses a waste silicate solution for hydrothermal preparation and no prior preparation is needed, production costs are estimated to be considerable lower where silicate solutions need to be prepared by base treatment, even if ash is used, as for the RHA derived MCM-41 used here.